Intermittent Theta Burst Stimulation vs. High-Frequency Repetitive Transcranial Magnetic Stimulation in the Treatment of Methamphetamine Patients - Liu, Qingming; Sun, Huimeng; Hu, Yitian; Wang, Qiongyao; Zhao, Zhiyong; Dong, Da; Shen, Ying (Frontiers in Psychiatry, 2022)
Background and Aims: In this brief report, we compare the effectiveness and safety of intermittent theta burst stimulation (iTBS) and conventional 10 Hz repetitive transcranial magnetic stimulation (rTMS) in patients with methamphetamine use disorder (MAUD). Our study suggests that iTBS would also reduce drug craving in patients with MAUD just as the 10 Hz; thus, there may be no difference in treatment effects between these two methods. Methods: Twenty male methamphetamine (MA) addicts were randomly assigned to iTBS (n=10) or 10 Hz (n=10) groups for 12 treatments. Cue-evoked cravings, anxiety, depression, and withdrawal symptoms were measured at baseline before the first treatment, and posttests after days 10, 15, and 20. Results: The results showed that iTBS and 10 Hz treatment had a similar effectiveness in reducing cue-induced craving in male addicts for MA. Both 10 Hz and iTBS improved withdrawal symptoms of patients with MAUD. Conclusions: iTBS may be similar in effectiveness as 10 Hz in treating patients with MAUD. The clinical usefulness of rTMS could be improved substantially due to the increase in its capacity, cost, and accessibility. Importantly, the effectiveness of rTMS in treatment of patients with MAUD is not yet proven, and should be tested in large double-blind sham-controlled studies.